Socioenvironmental Risk Factors for Adolescent Marijuana Use in a United States-Mexico Border Community - Valdez, Elizabeth Salerno (Am J Health Promot, 2020)
PURPOSE: We examined how socioenvironmental risk factors unique to the United States-Mexico border, defined as border community and immigration stress, normalization of drug trafficking, and perceived disordered neighborhood stress, contribute to tobacco, alcohol, and marijuana use among adolescents residing there. DESIGN: Cross-sectional design. SETTING: The study was conducted at a high school on the United States-Mexico border. SUBJECTS: A sample of 445 primarily Hispanic students (ages 14–18). MEASURE: Perceived Disordered Neighborhood Stress Scale, Border Community and Immigration Stress Scale, and Normalization of Drug Trafficking Scale. ANALYSIS: Logistic regression assessed the association between the socioenvironmental risk factors and past 30-day tobacco, alcohol, and marijuana use. RESULTS: Participants with higher border community and immigration stress scores were significantly more likely to have used tobacco (adjusted odds ratio [aOR] = 1.41, P < .01) and alcohol (aOR = 1.31, P < .01) in the past 30 days. Perceived disordered neighborhood stress also was associated with past 30-day alcohol use (aOR = 1.46, P < .00). The normalization of drug trafficking was associated with past 30-day marijuana use (aOR = 1.45, P < .05). CONCLUSIONS: Public health practitioners, educational institutions, and policy makers should consider the economic and normative environment of the United States-Mexico border for future substance use prevention and risk reduction efforts targeting border adolescents.